Rating training load of disabled swimmers in general preparation sub-period - Bolach, B.; Seidel, W.; Mrozkowiak, M. (Central European Journal of Sport Sciences and Medicine, 2020)
The aim of the work was to assess the training loads of disabled swimmers in the comprehensive preparation sub-period. The research was carried out on 12 swimmers of the WZSN "START" Wroclaw swimming club section. All swimmers started in the "S" start group. The average age of swimmers was 24 years and the average training time was 8 years. The pulse rates were analyzed 6 times during the training, just before the training, in the 10th minute of the warm-up, in the 45th minute at the peak of the training, in the 80th minute, in the 90th minute immediately after the training, and in the 105th minute after the rest. A Polar 810i Sport-tester was used to evaluate the heart rate. Statistical analysis was used. For all the swimmers the average heart rate values after 15 minutes of rest did not return to resting heart rate values. In addition, the swimmer`s fatigue was assessed using the Borg scale. The training load was moderate, and on the Borg scale, the swimmers assessed their fatigue as very heavy.